Association of Glycated Proteins with Inflammatory Proteins and Periodontal Disease Parameters. (11th January 2020) - Panezai, Jeneen; Altamash, Mohammad; Engstrӧm, Per-Erik; Larsson, Anders
Abstract : Periodontitis is a chronic inflammatory condition that may contribute to diabetogenesis. The aim was to investigate the levels of glycated proteins and their correlation with periodontal and systemic inflammation. Fifty-one patients with periodontitis and 20 healthy subjects underwent probing pocket depth (PPD) measurements. PPD total and PPD disease with and without tooth adjustment were used as continuous indices. Marginal bone loss (MBL) for mandibular premolars and molars was measured digitally. Body mass index (BMI) and waist circumference (WC) were also analyzed. Glycated hemoglobin (HbA1c) and fructosamine (FrAm) levels were measured in all subjects. A multiplex proximity extension assay (PEA) was used to analyze the serum samples for simultaneous measurement of 92 proteins. Both HbA1c and FrAm inversely correlated with IL-10, FGF-21, MCP-1, and TNF beta amongst 16 proteins. HbA1c correlated directly with OPG. Parameters of disease severity were consistently significant for HbA1c. Adjusted PPD total and number of missing teeth were increased in diabetes whereas levels of RANKL and RANKL to OPG ratio were the highest in nondiabetic periodontitis patients. Hyperglycemic conditions in periodontitis patients are associated with reduced levels of anti-inflammatory proteins as well as dysregulated bone resorption.